Exploring the complex interplay: gut microbiome, stress, and leptospirosis - Petakh, Pavlo; Oksenych, Valentyn; Kamyshna, Iryna; Boisak, Iryna; Lyubomirskaya, Katerina; Kamyshnyi, Oleksandr (Frontiers in Microbiology, 2024)
Leptospirosis, a re-emerging zoonotic disease, remains a significant global health concern, especially amid floods and disasters such as the Kakhovka Dam destruction. As is known, the stress that occurs in the conditions of military conflicts among civilian and military personnel significantly affects susceptibility to infectious diseases and possibly even influences their course. This review aims to explore how the gut microbiome and stress mediators (such as catecholamines and corticosteroids) might impact the leptospirosis disease course. The review opens new horizons for research by elucidating the connections between the gut microbiome, stress, and leptospirosis.